Design and development of 3D Face Mask Clips for Hijab - Ahmad Sofian, Shminan; Khan, Rehman Ullah; Wan Norizan, Wan Hashim (Journal of Cognitive Sciences and Human Development, 2020)
The world has suffered a critical shortage of Personal Protective Equipment (PPE) during the pandemic of COVID19 for medical staffs, the front liners. Like the whole world, Malaysia also imposed the stay-at-home and Movement Control Order (MCO) to break the chain of infections and flatten the curve of cases. The supply of PPE became a challenge during the lock down. There have been joined efforts from various parties stepping up, with different ways to help the production process of these key equipment but mostly focus on PPTs for male. Another challenge was face mask for Muslims leady health workers who wear hijab. This paper is about how to overcome these challenges and designed a novel face mask clip for hijab, using 3D printing. The clips were tested in a local hospital. The results show that the clips are very effective and easy to use.